Crystal Structure of PigA: A Prolyl Thioester‐Oxidizing Enzyme in Prodigiosin Biosynthesis. (11th October 2018) - Lee, Cheng‐Chung; Ko, Tzu‐Ping; Chen, Chun‐Ting; Chan, Yueh‐Te; Lo, Shin‐Yi; Chang, Jen‐Yu; Chen, Ya‐Wen; Chung, Ting‐Fang; Hsieh, Hsin‐Ju; Hsiao, Chwan‐Deng; Wang, Andrew H.‐J.
Abstract: Prodigiosin is an intensely red pigment comprising three pyrroles. The biosynthetic pathway includes a two‐step proline oxidation catalyzed by phosphatidylinositol N ‐acetylglucosaminyltransferase subunit A (PigA), with flavin adenine dinucleotide (FAD) as its cofactor. The enzyme is crystallized in the apo form and in complex with FAD and proline. As an acyl coenzyme A dehydrogenase (ACAD) family member, the protein folds into a β‐sheet flanked by two α‐helical domains. PigA forms a tetramer, which is consistent with analytical ultracentrifugation results. FAD binds to PigA in a similar way to that in the other enzymes of the ACAD family. The variable conformations of loop β4–β5 and helix αG correlate well with the structural flexibility required for substrate entrance to the Re side of FAD. Modeling with PigG, the acyl carrier protein, suggests a reasonable mode of interaction with PigA. The structure helps to explain the proline oxidation mechanism, in which Glu244 plays a central role by abstracting the substrate protons. It also reveals a plausible pocket for oxygen binding to the Si side of FAD. Abstract : FAD binding : The biosynthesis of the red dye prodigiosin includes a two‐step proline oxidation catalyzed by the enzyme PigA, with flavin adenine dinucleotide (FAD) as its cofactor. The FAD and proline binding modes are clearly shown by XRD at 1.3 and 1.6 Å resolution. A PigA/prolyl‐PigG complex model explains the catalytic mechanism.